Maternal high-fat diet during lactation increases Kiss1 mRNA expression in the arcuate nucleus at weaning and advances puberty onset in female rats. (November 2015) - Takumi, Ken; Shimada, Kousuke; Iijima, Norio; Ozawa, Hitoshi
Highlights: Maternal high-fat diet (HFD) during lactation induced early puberty onset. Maternal HFD increased Kiss1 expression in the arcuate nucleus (ARC) at weaning. HFD female pups showed increases in adipocyte size and serum leptin levels. Prepubertal leptin administration had no effect on Kiss1 expression at weaning. An early increase in Kiss1 expression in the ARC might accelerate puberty onset. Abstract: Nutrition has significant influences on the development of reproductive functions. Post-weaning manipulation of nutritional status has been shown to alter puberty onset accompanied by changes in the expression of kisspeptin, a neuropeptide encoded by the Kiss1 gene which plays important roles in pubertal development. However, information about the influence of overnutrition during early development is sparse. In this study, we examined pubertal development and Kiss1 mRNA expression in female pups reared by dams fed a high-fat diet (HFD) during lactation. Maternal HFD significantly increased body weight and accelerated puberty onset of female offspring. The number of Kiss1 -expressing neurons in the arcuate nucleus (ARC) at weaning was significantly greater in pups of HFD-fed dams than in pups of dams fed a normal diet (ND), whereas no significant difference was observed in the anteroventral periventricular nucleus, the other Kiss1 -expressing nucleus. Because adipocyte size and serum leptin level were increased in HFD offspring, we examined the effects of exogenous leptin during the pre-weaning period on Kiss1 expression. Unexpectedly, exogenous leptin had no effect on Kiss1 expression. In summary, we demonstrate that a maternal HFD during the early postnatal period induces increased Kiss1 expression in the ARC and early puberty onset in female offspring.